Objects, Words, and Religion: Popular Belief and Protestantism in Early Modern England - Ludwikowska, Joanna (Studia Anglica Posnaniensia, 2017)
This article deals with selected aspects of popular belief in post-Reformation England as compared to the pre-Reformation popular tradition of the fourteenth and fifteenth century. Through a discussion of the politics of superstition and religiously-shaped concepts of reason in Early Modern England, this article discusses medicinal magic, and the power of objects and words in the context of religion and popular belief, focusing in particular on leprosy and exorcism. By examining the Protestant understanding of the supernatural as well as its polemical importance, the article investigates the perseverance of popular belief after the Reformation and outlines some of the reasons and politics behind this perseverance, while also examining the role of the supernatural in the culture of belief in Early Modern England by tracing the presence and importance of particular beliefs in popular imagination and in the way religion and confessional rhetoric made use of popular beliefs.